2016
DOI: 10.1080/00222895.2016.1152224
|View full text |Cite
|
Sign up to set email alerts
|

Focus of Attention in Children's Motor Learning: Examining the Role of Age and Working Memory

Abstract: The authors investigated the relative effectiveness of different attentional focus instructions on motor learning in primary school children. In addition, we explored whether the effect of attentional focus on motor learning was influenced by children's age and verbal working memory capacity. Novice 8-9-year old children (n = 30) and 11-12-year-old children (n = 30) practiced a golf putting task. For each age group, half the participants received instructions to focus (internally) on the swing of their arm, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
56
1
7

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 30 publications
5
56
1
7
Order By: Relevance
“…Children with low working memory capacity did not show learning. In contrast, two other recent studies involving children, both typically developing children and children with severe motor difficulties, did not find support for the conjecture that working memory capacity is associated with learning (Brocken, Kal, & van der Kamp, 2016;Jongbloed-Pereboom, Peeters, Overvelde, Nijhuis-van der Sanden, & Steenbergen, 2015). The relationship between working memory capacity and performance during practice (or acquisition performance) was not assessed in these studies.…”
contrasting
confidence: 65%
See 1 more Smart Citation
“…Children with low working memory capacity did not show learning. In contrast, two other recent studies involving children, both typically developing children and children with severe motor difficulties, did not find support for the conjecture that working memory capacity is associated with learning (Brocken, Kal, & van der Kamp, 2016;Jongbloed-Pereboom, Peeters, Overvelde, Nijhuis-van der Sanden, & Steenbergen, 2015). The relationship between working memory capacity and performance during practice (or acquisition performance) was not assessed in these studies.…”
contrasting
confidence: 65%
“…An obvious one is the nature and content of the instructions. For example, Brocken et al (2016) recently showed that children benefit more from instructions that direct attention toward the effects of the movement, rather than toward the execution of the movement as in the present study. In addition, not all instructions are equally meaningful for facilitating learning in novices; we developed the instructions in collaboration with an expert boccia coach.…”
Section: The Roles Of Working Memory Capacity and Declarative Knowledmentioning
confidence: 52%
“…The current findings add important evidence to the increasing body of literature showing a lack, or an unexpected role of working memory for motor learning of children (Brocken, Kal, & van der Kamp, 2016;Jongbloed-Pereboom, Peeters, Overvelde, Nijihuis-van der Sanden, and Steenbergen (2015); Krajenbrink et al, 2018;van Abswoude, Nuijen et al, 2018;van Abswoude, van der Kamp, & Steenbergen, 2018). For example, in a recent study, van van Abswoude, van der Kamp et al, 2018 found only a small effect of visuospatial working memory capacity on performance during practice of an aiming task in an explicit context.…”
Section: Discussionsupporting
confidence: 71%
“…However, this effect was not present for retention one day later. Brocken et al (2016) also failed to show a role for working memory capacity on learning with an internal or external focus of attention, although they only investigated verbal working memory. Finally, in the studies of Krajenbrink et al (2018) and van van Abswoude, Nuijen et al (2018) there was also no role of working memory capacity for respectively learning over a one week period, and performance during practice, with internal or external focus instructions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation